Pengaruh Kecerdasan Emosional, Intergitas dan Independensi Auditor Terhadap Kualitas Audit - Putri, Okti Isra; Fauzihardani, Eka (Jurnal Nuansa Karya Akuntansi, 2025)
The purpose of this study is to determine whether there is an influence of emotional intelligence, integrity and independence on audit quality in Public Accounting Firms in Padang City. The population in this study were all auditors of Public Accounting Firms in Padang City as many as 60 people. The type of data used is primary data by distributing questionnaires. The analysis technique used is multiple linear regression analysis technique. The test results show that emotional intelligence has a positive effect on audit quality, while integrity and independence do not affect audit quality. Suggestions for further research are better expanded and increase the number of samples in the study and, variables in further research should be added with other variables.